Eliminar barreras comunicativas: documentos digitales accesibles, reto para la educación superior - Baquero Vargas, Natalia Brigith; Buitrago Sánchez, Diana Carolina; Forero Garzón, Ivonne Geraldyn; Gutiérrez Sánchez, Luisa María; Laiton López, Anyela Lorena; Romero Castro, Julieth Dayana; Villamil Hernández, María José (Lee La LEE, 2023)
Eliminar barreras comunicativas: documentos digitales accesibles, reto para la educación superior